Properties of Stretchable Graphite Intercalation Compound/Polydimethylsiloxane Composites after Cyclic Tensile Strain of 20% - Park, Gyu-Dae; Choi, Won-Kook; Lee, Sung-Goo; Kim, Kyung-Min; Kim, Sung-Ryong (POLYMER SOC KOREA, 2016)
The expanded graphite intercalated compound (GIC)/poly(dimethyl siloxane) (PDMS) composites were prepared and the effects of cyclic stretching on the morphology, thermal conductivity and surface resistance of the composites were investigated. PDMS resin did not penetrate into the pores of the expanded GIC. The uniform distribution and spatially connected GICs in the PDMS matrix resulted in improved thermal conductivity and decreased sheet resistance. The thermal conductivity and sheet resistance of GIC(20 wt%)/PDMS composites were changed after 1000 cycles of 20% tensile strain from 0.80 W/mK and 6x1013 Q/sq to 0.69 W/mK and 3.04x10(14) Q/sq, respectively. The decreased thermal conductivity and the increased sheet resistance of the composites after cyclic stretching was attributed to the formation of the interfacial crack between PDMS matrix and the GIC filler.